1999
DOI: 10.1002/(sici)1097-0290(19990120)62:2<200::aid-bit10>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects and biotransformation of acrylic acid in computer-controlled pH-Stat CSTRs

Abstract: In this study, the inhibitory effects and anaerobic biotransformation of acrylic acid in computer‐controlled pH‐stat completely stirred tank reactors (CSTRs) with two different cultures, namely unacclimated and acrylate‐acclimated acetate‐enriched Methanosarcina and homogenized (crushed) granular cultures, were investigated. The microbial acclimation, influent concentration, and loading rate of acrylic acid were studied in the experiments. The experimental results revealed that methanogenic cultures at a conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
3
0
3
Order By: Relevance
“…The reactors (R1, R2, R3, and R4) were operated as pH-stat CSTRs (Demirer and Speece, 1999). The pH-stat CSTR system consisted of a magnetically stirred glass reactor of 1-L effective volume with a headspace of 500 mL (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The reactors (R1, R2, R3, and R4) were operated as pH-stat CSTRs (Demirer and Speece, 1999). The pH-stat CSTR system consisted of a magnetically stirred glass reactor of 1-L effective volume with a headspace of 500 mL (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Attempts for removal of these compounds have been made in anaerobic conditions, but results have been poor (Dangcong & Xingwen 1994;Araya et al 1999Araya et al , 2000. It is said that the main limiting step is the inhibition of the methanogenic activity produced by the concentration of polymeric resins compounds (PRC) and the accumulation of intermediates (Stuckey et al 1980;Grbić -Galić et al 1990;Demirer & Speece 1999). Most of the studies under anaerobic conditions have shown that the problems in the treatment of the wastewater are the compounds conforming the resins.…”
Section: Introductionmentioning
confidence: 99%
“…La utilización de sustratos primarios en la degradación de ácido acrílico está poco documentada, en algunos estudios se han utilizado altas concentraciones de acetato (2000 mg•L -1 ), no obstante se requieren largos periodos de aclimatación (300 días) para degradar una carga orgánica volumétrica de 220 mg•L -1 •d -1 de este ácido (Demirer y Speece, 1999).…”
Section: Antecedentesunclassified
“…Aunque los periodos de recuperación en este estudio parecen prolongados, se ha reportado que en un cultivo enriquecido con Methanosarcina utilizando acetato (2000 mg•L -1 ) como sustrato primario, 900 mg•L -1 de ácido acrílico causaron inhibición sobre las bacterias utilizadoras de acetato y propionato, requiriendo un periodo de 44 días para recuperar la actividad sobre estos sustratos en reactores de tanque agitado. Mientras que para un cultivo homogenizado y en el que predominaban bacterias acetogénicas y metanogénicas después de 50 días de inhibición el ácido acrílico fue consumido como único sustrato (Demirer y Speece, 1999).…”
Section: Comparación De La Degradación Del áCido Acrílico Y Alcoholes...unclassified
See 1 more Smart Citation